Laughter in the Poetry of Francisco Álvarez de Velasco y Zorrilla (2017)
Rhythmica sacra, moral y laudatoria [Sacred, moral and laudatory rhythmics] (1703), by Álvarez de Velasco y Zorrilla, is a unique Neogranadian document that studies the diverse expressions of laughter in Colonial poetry. Firstly, we show the exclusion of laughter in the “high culture”, and the consequent writing of non-burlesque satires. As a side objective, in these poems we also analyze the creole appropriation of Peninsular models. Secondly, we study the works associated with religious rituals and the persistence of laughter in the common people. Thirdly, we propose an intermediate field in the laudatory letters to Sor Juana, where laughter becomes independent from these rituals and initiates the way to modernity